School Counseling Services and Students’ Psychological Recovery After the 2025 Hydrometeorological Disaster in Central Aceh - Husrin Konadi; Hernita Hernita; Riyan Pujiono (Era Scientific Publisher, 2026)
Hydrometeorological disasters frequently affect vulnerable communities in Indonesia and often result in significant psychological consequences for children and adolescents. This study aimed to examine the psychological impacts experienced by students following the 2025 hydrometeorological disaster in Central Aceh, analyze the role of school counseling services in supporting students’ recovery, and identify challenges in the implementation of post-disaster counseling interventions. The study employed a qualitative case study design involving 25 disaster-affected students, 12 school counselors, and 10 subject teachers from several elementary and secondary schools in Central Aceh. Data were collected through semi-structured interviews, non-participant observations, and document analysis. The data were analyzed using the interactive model of Miles, Huberman, and Saldaña, including data condensation, data display, and conclusion drawing. The findings revealed that students experienced various psychological difficulties, including anxiety, recurring fear, concentration problems, sleep disturbances, and decreased learning motivation. School counseling services, implemented through individual counseling, group counseling, classroom guidance, and trauma-healing activities, played a significant role in facilitating students’ psychological recovery and strengthening their resilience. However, the effectiveness of these services was constrained by limited numbers of counselors, insufficient trauma-related training, inadequate facilities, and restricted service time. The study concludes that school counseling services constitute an essential component of post-disaster recovery and should be strengthened through enhanced professional capacity, integrated psychosocial support programs, and collaboration among schools, local governments, and mental health stakeholders. The findings contribute to the development of disaster-responsive counseling practices and school-based psychosocial support systems in disaster-prone regions.